Women, family, pluralism and the law in Malaysia - Shuaib, Farid Sufian (2017)
Legal pluralism where different laws apply to different group of people is the realities in Malaysia. Malaysia is a Muslim majority country with a substantial number of adherents of other religions such as Hinduism, Buddhism, Christianity, Sikhism and animism. She has a colourful history with regards to assorted religious, cultural and legal influences from her past, including the pre-colonial and post-colonial era (Hooker, 1986). These influences were the result of trading activities, colonialism and movement of people from various parts of the world including from the Indian subcontinent and China (Comber, 2009). These influences sculptured her legal system into a pluralism granting legal realities reflected as constitutional guarantees in the language of status and rights (Shuaib, 2008). This legal pluralism where colonial law co-exist with indigenous law and customs of immigrants means that different laws, in particular personal laws, apply to the different ethnic and religious groups (Ibrahim, 1987). The pluralistic laws cover issues affecting women and family, such as the issue of marriage and custody of children. Being a plural society in terms of religion, culture and ethnicity, these legal arrangements are not without contention, controversy and strife (Lee, 1995). Questions may be raised as to whether applying different laws to women from different communities is consistent with the idea of justice (Menski, 2006). The State does not view this as discrimination (Malaysia, 2016). Taking into account the sometime simmering stressed ethnic and religious relations in the history of Malaysia, the writing of a constitution for an independent Malaya (the former name for Malaysia) represents the basic agreement between different ethnic and religious groups in casting the shape of the nation (Harding, 1996). This paper looks at this state of affairs and offers explanations and suggestions. The paper adopts a doctrinal approach in conducting the research and makes reference to legislative instruments such as the constitution, statutes and decision of the courts. The paper also looks at recent legislative attempts to resolve various grievances resulting from legal pluralism.